Diversity and composition of Crustacean and Mollusk in mangrove area of Sampang and Pamekasan Districts, Madura Island, Indonesia - MUHAMMAD RAHARDIAN, ADILA HAQQI; DAMAYANTI MIFTACHUS, SHOLICHAH; JILAN, ASHILA; ANGGI DWIKI, REZA; MUHAMMAD, INDRAWAN; MUH. SULAIMAN, DADIONO; CHEE, KONG YAP; Khairul Adha, A. Rahim; AHMAD DWI, SETYAWAN (Smujo.id, 2026)
Haqqi MRA, Sholichah DM, Ashila J, Reza AD, Indrawan M, Dadiono MS, Yap CK, Rahim KABA, Setyawan AD. 2024. Diversity and composition of Crustacean and Mollusk in mangrove area of Sampang and Pamekasan Districts, Madura Island, Indonesia. Indo Pac J Ocean Life 8: 59-71. Mangrove ecosystem in Indonesia is the largest in the world and contains various biota with a great interest to study. An example of mangrove ecosystems can be found in Sampang and Pamekasan Districts, Madura Island which have a high potential for biodiversity, such as Crustacean and Mollusk. However, information regarding the diversity of Crustaceans and Mollusks in that territory is still very limited. Therefore, this research was conducted to assess the diversity of Crustaceans and Mollusks in the mangrove area of Sampang and Pamekasan Districts. The study was conducted in December 2023 with data collection located at four stations: (i) Taddan, Camplong Sub-district and (ii) Song-Osong Beach, Sampang Sub-district, both in Sampang District; (iii) Branta Tinggi and (iv) Raya Ambat Street both in Tlanakan Sub-district, Pamekasan District. Data on biotic and abiotic environmental parameters was collected and sampling of Crustacean and Mollusk was conducted using Visual Encounter Survey (VES) and direct catching. The results showed that mangrove ecosystem in Sampang and Pamekasan Districts had certain similarities, i.e. both were composed by vegetation of Sonneratia alba, Avicennia marina, Sonneratia caseolaris, and Rhizophora mucronata. The environmental parameters measurement showed that the study area location has warm temperatures, wet soil, neutral pH, and relatively low salinity compared to Madura Strait. There were 32 Crustacean species with the mostly found was Balanus sp. (barnacle), followed by Clibanarius longitarsus (common hermit crab). The number of Mollusks obtained was 24 species with the mostly found was Pirenella alata and Pirenella cingulata. Based on ecological indices calculation, Crustacean on study area location had moderate diversity, high species richness, high evenness or stable community, and indicates no dominant species. While the Mollusk on study area location had moderate diversity, moderate species richness, high evenness or stable community, and indicates no dominant species. Station 3 (Branta Tinggi) had the highest number of Crustacean species, diversity, species richness, and evenness, while Station 4 (Raya Ambat Street) had the highest number of Mollusk species, diversity, species richness, and evenness.